Nanoscale Characterization of Glass Flake Filled Vinyl Ester Anti-Corrosion Coatings - Barbhuiya, Salim; Choudhury, M. (MDPI AG, 2017)
Vinyl ester is a thermoset matrix resin that is widely used in the coating industry. The presence of glass flakes further enhances the anti-corrosion performance of this coating. This paper reports the nanoscaled characterization of glass flake filled vinyl ester anti-corrosion coatings on mild steel. Bond strength properties of one uncoated and four coated samples with different thicknesses (300, 600, 900 and 1200 μm) were studied using nanoscratch technique and ASTM Standard Test. It was found that the bond strength of coating with thickness 900 μm was the highest. The frequency distributions of elastic modulus on coating with 900 μm thickness determined using nanoindentation indicated that only 20–25% of the coating is composed of glass flakes and the balance is vinyl ester matrix. The critical depth at which the material is subject to failure due to external load and abrasion, was found to be around 100 nm.